Sclerotinia sclerotiorum Thioredoxin Reductase Is Required for Oxidative Stress Tolerance, Virulence, and Sclerotial Development - Zhang, Jinyi; Wang, Yabo; Du, Jiao; Huang, Zhiqiang; Fang, Anfei; Yang, Yuheng; Bi, Chaowei; Qing, Ling; Yu, Yang (Frontiers in Microbiology, 2019)
Sclerotinia sclerotiorum is a destructive ascosmycete plant pathogen with worldwide distribution. Extensive research on different aspects of this pathogen’s capability to cause disease will help to uncover clues about new ways to safely control Sclerotinia diseases. The thioredoxin (Trx) system consists of Trx and thioredoxin reductase (TrxR), which play critical roles in maintenance of cellular redox homeostasis. In this study, we functionally characterized a gene encoding a TrxR (SsTrr1) in S. sclerotiorum. The amino acids of SsTrr1 exhibited high similarity with reported TrxRs in plant pathogens and targeted silencing of SsTrr1 lead to a decrease in TrxR activities of mycelium. SsTrr1 showed high expression levels during hyphae growth, and the levels decreased at the different stages of sclerotial development. SsTrr1 gene-silenced strains produced a smaller number of larger sclerotia on potato dextrose agar (PDA) medium. The observations were consistent with the inhibitory effects on sclerotial development by the TrxR inhibitor, anrunofin. The expression of SsTrr1 showed a dramatic increase under the oxidative stress and the hyphal growth of gene-silenced strains showed more sensitivity to H2O2. SsTrr1 gene-silenced strains also showed impaired virulence in different hosts. Taken together, our results suggest that SsTrr1 encodes a TrxR that is of great important for oxidative stress tolerance, virulence and sclerotial development of S. sclerotiorum.